Modification of Co/Al2O3 Fischer–Tropsch Nanocatalysts by Adding Ni: A Kinetic Approach. Issue 3 (25th January 2016) - Nikparsa, Paria; Mirzaei, Ali Akbar; Rauch, Reinhard
ABSTRACT: In this article, the effects of Ni (Co:Ni ratio = 4:1) on the performances and kinetic parameters of Co/Al2 O3 nanocatalysts are explored in Fischer–Tropsch synthesis. As a result, the probability of chain growth increases and the deactivation rate decreases with addition of Ni. The properties of catalysts are characterized at different stages using Brunauer–Emmett–Teller analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, and the vibrating sample magnetometer technique. The Co/Ni/Al2 O3 catalyst with higher surface area and pore size exhibits higher activity and C5+ selectivity. The different results obtained for room‐temperature ferromagnetism have been attributed to the different metal oxides in the catalysts. The Fischer Tropsch kinetic study is done on the basis of the Langmuir–Hinshelwood–Hougen–Watson adsorption theory. Seven kinetic expressions based on the carbide and enolic mechanisms are selected. All experimental data are theoretically examined with these kinetic expressions to derive the best kinetic according to the linear and nonlinear approaches. The kinetic parameters of the fitted model, including the rate constant ( k ) and activation energy ( Ea), are calculated with the Levenberg–Marquardt and genetic algorithm. The results show that by adding Ni the activation energy ( E a ) decreases, the reaction rate (– R CO ) increases, and the CO adsorption on the Co/Ni/Al2 O3 catalyst is faster as well.